COMPULSIVE BUYING AND DEBT BEHAVIOR (DISSAVING) OF MILLENNIAL GENERATION IN DENPASAR CITY - NOVITASARI, I GUSTI AYU (Universitas Mahasaraswati K. Mataram, 2023)
The tendency to take debt for consumptive buying is a habit that is often carried out by the millennial generation. Study aiming to analyze the link between compulsive buying with debt behavior in the millennial generation in Denpasar City with a sample of 200 respondents. Data collection through the distribution of google form questionnaires. Statistical analysis using multiple linear regression. Study found that compulsive buying has positive significant effect towards debt behaviour